Detection of Emergence Cyclospora cayetanensis in A HIV+ /AIDS Patient with Diarrhea from Tehran: A Case Report - Khadijeh KHANALIHA; Mehdi MOHEBALI; Setareh DAVOUDI; OmidREZA HOSSEINI; Fatemeh TARIGHI; Tahereh REZAEIAN; Mostafa REZAEIAN (Tehran University of Medical Sciences, 2015)
Coccidian protozoa of Cyclospora cayetanensis are obligate intracellular apicomplexan parasites that infect the mucosal epithelium of the small intestine of immunocompetent and immunocompromised persons. A 25- years old woman from around, Tehran with complaint of faintness and fatigue with HIV positive/AIDS confirmed eight months ago was admitted in Imam Khomeini Hospital, Tehran, Iran in 2014. The patient suffered from intestinal and lung symp-toms like watery diarrhea, flu-like symptoms. The stool was examined by direct preparation and concentration tech-nique, stained with modified acid-fast staining method, and observed with light and then Immunofluorescence micro-scope. The stool cultivation was made in dichromate potassium medium and diagnosis of Cyclospora infection was fi-nally made according to observation of Cyclospora oocysts almost 10 μm in acid-fast staining method and autofluores-cence of Cyclospora under Immunofluorescence microscope. The patient was initially treated with azithromycin, tazocin and fluconazol because of lung lesions and diarrhea and relative remission was observed. Cyclospora sp. causes an intes-tinal infection particularly in immunocompromised patients.